Evaluating E-Government Web Usability : A Case Study of Penang.Net - Gan, Min Choo (2005)
Electronic Government (E-Government) initiatives have often sounded very promising but been difficult to implement. Therefore, it is important to ensure that people, have opportunities to benefit from the Web by the government, especially from on-line public services or the online information. The study takes into consideration how E-Government should be understood. It presents the review of literature regarding the examination on E-government evaluation methods adopted in leading information technology advanced countries. This study aims to provide usability evaluation of the Penang state E-Government web sites: Penang.Net by using the benchmarking approach by using a form of the benchmark approach to asess the degree to which each of the web site usability and the contents usefulness. By then it contrasts the web page of the three web sites and a discussion of the best practice for various usability criteria. The result of this study can be used to inform the subsequent re-design of the Penang.Net home page. The finding is intended to measure the performance and quality of Penang.Net web against the others state government service website. The suggested guidelines established in this study aimed to provide suggestions to the Penang state government that enables then to produce E-Government web sites that are both usable and benefit to Penang people.